The Teacher Professional Education Program (PPG) Graduates’ Interest, Motivation, Self-Efficacy, and Instructional Practices in Implementing Culturally Responsive English Teaching (CRET) within the Merdeka Curriculum - Muhammad Agung; Sutrah; Khaeril Mujahid; Muhammad Tahir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The global educational paradigm has moved beyond knowledge transmission to focus on holistic competencies, a transition mirrored in Indonesia’s Merdeka Curriculum with its emphasis on contextual relevance, learner differentiation, and the Pancasila Student Profile. Within English language education, this mandates a pedagogical reorientation, for which Culturally Responsive English Teaching (CRET) presents a critical framework, positioning students’ cultural backgrounds as foundational assets for instruction. As the primary agents of this reform, teachers’ capacity to implement CRET is paramount, with the Teacher Professional Education Program (PPG) serving as a key conduit for professional readiness. However, the specific preparedness of PPG graduates, a cohort strategically trained for curricular innovation, remains empirically unverified. This quantitative correlational study investigates the relationships between PPG graduates’ psychological dispositions (interest, motivation, self-efficacy), their general instructional practices, and the quality of CRET implementation within the Merdeka Curriculum. Data from purposively sampled Indonesian EFL teachers (n=121) were analyzed to determine correlational strength and predictive power. Results revealed that while descriptive levels of interest, motivation, self-efficacy, and CRET-aligned practices were high, only self-efficacy and instructional practices demonstrated significant positive correlations with implementation quality. Notably, multiple regression analysis identified self-efficacy as the strongest positive predictor, whereas interest emerged as a significant negative predictor when other variables were controlled. This counterintuitive finding suggests that isolated theoretical interest, without corresponding practical competence or contextual support, may not translate into effective classroom enactment, suggesting potential contextual or translational barriers between disposition and enactment. The findings underscore the complexity of translating pedagogical commitment into practice, highlighting that systemic professional development must extend beyond fostering theoretical interest to strategically building applied, context-specific competence and efficacy. Consequently, PPG programs should prioritize experiential learning, such as mentored practicums focused on CRT, to bridge the gap between pedagogical interest and actionable skill.